Putting fitness to the test: clinical application of the Fitkids Treadmill Test in youth with chronic pain. (2nd January 2022) - Shulman, Julie; Smith, Allison; Keysor, Julie; Kenney, Anne; Damice, Brittany; DeFabio, Roxanne; Jervis, Kelsey; Zurakowski, David; Sethna, Navil
Abstract: Purpose: Examine the clinical utility of the Fitkids Treadmill Test (FTT) for assessing cardiovascular endurance in youth with chronic pain. Materials and methods: Fifty-five youth with chronic pain completed the FTT at admission and discharge from intensive interdisciplinary pain treatment (IIPT). Feasibility, construct validity and responsiveness of the FTT were examined retrospectively using a clinical data registry. Results: Participants' FTT time to exhaustion (TTE) improved by 1.5 min after IIPT (95% CI: 1.1–2.0 min), yet remained below age and sex-matched norms. Construct validity was only supported by performance-based assessments of physical function. Evidence of discriminant validity was found, as the FTT was not correlated with unrelated biopsychosocial constructs. Conclusions: Youth with chronic pain present with significant deficits in cardiovascular endurance that are not fully reversed after IIPT, highlighting the importance of ongoing aerobic training after discharge. Findings support the FTT as a valid, objective measure of cardiovascular endurance in youth with chronic pain. FTT performance is relatively unencumbered by psychosocial constructs.